Repurposing and recycling wind turbine blades in the United States. Issue 1 (22nd June 2022) - Martini, Ryan; Xydis, George
Abstract: Wind energy is increasing in popularity worldwide as a low‐cost, carbon‐free energy technology. As deployment continues to grow, owners will need to conduct planning for end‐of‐life strategies for the components that are large in volume, number, and not readily recyclable in the operational form. Since the first modern, utility‐scale wind turbines were installed in the 1990s, a large number of wind turbines are reaching their end‐of‐life (typically 20–25 years) and each year an increasing number of blades are decommissioned. To stimulate efficient turbine reuse and recycling industry, industry and public funding should be allocated to support: research and testing processing methods, implementing potential applications of the material, and incentivizing successful applications for reuse of the material. Since the blades are the component most exposed to the elements and least easily recycled, this work will focus on their post‐operation applications. This work discusses the current literature on wind turbine blade reuse and recycling, proposing suggestions for applications of the materials and policy support. The work also estimates that by the years 2043–2050, only based on the development zones announced on the East Coast, a cumulative of 2.4 million metric tons (t) of wind blades would be needed to be repurposed and recycled.